Dihydromyricetin Modulates Nrf2 and NF-κB Crosstalk to Alleviate Methotrexate-Induced Lung Toxicity - Asmaa I. Matouk; Eman M. Awad; Nashwa F. G. El-Tahawy; Azza A. K. El-Sheikh; Aliaa Anter (MDPI AG, 2023)
Background: Methotrexate (MTX) is an effective anticancer, anti-inflammatory, and immunomodulatory agent. However, it induces a serious pneumonitis that leads to irreversible fibrotic lung damage. This study addresses the protective role of the natural flavonoid dihydromyricetin (DHM) against MTX-induced pneumonitis via modulation of Nrf2/NF-κB signaling crosstalk. Methods: Male Wistar rats were divided into 4 groups: control, which received the vehicle; MTX, which received a single MTX (40 mg/kg, i.p) at day 9 of the experiment; (MTX + DHM), which received oral DHM (300 mg/kg) for 14 days and methotrexate (40 mg/kg, i.p) on the 9th day; and DHM, which received DHM (300 mg/kg, p.o) for 14 days. Results: Lung histopathological examination and scoring showed a decline in MTX-induced alveolar epithelial damage and decreased inflammatory cell infiltration by DHM treatment. Further, DHM significantly alleviated the oxidative stress by decreasing MDA while increasing GSH and SOD antioxidant levels. Additionally, DHM suppressed the pulmonary inflammation and fibrosis through decreasing levels of NF-κB, IL-1β, and TGF-β1 while promoting the expression of Nrf2, a positive regulator of antioxidant genes, and its downstream modulator, HO-1. Conclusion: This study identified DHM as a promising therapeutic target against MTX-induced pneumonitis via activation of Nrf2 antioxidant signaling while suppressing the NF-κB mediated inflammatory pathways.